Reconstruction of large wounds using a combination of negative pressure wound therapy and punch grafting after excision of acral lentiginous melanoma on the foot. Issue 1 (14th July 2015) - Seo, Jimyung; Kim, Jihee; Nam, Kyoung Ae; Zheng, Zhenlong; Oh, Byung Ho; Chung, Kee Yang
Abstract: Melanoma in darker‐pigmented individuals often develops in an acral lentiginous fashion on the foot. After surgical removal of a tumor at this site, repair of the wound can be challenging. This is because there is an insufficient local skin pool and lack of mobility of the skin in this area. Moreover, functional aspects such as walking and weight bearing should be considered. We performed a combination treatment of negative pressure wound therapy (NPWT) and punch grafting on 15 patients, after wide excision of acral lentiginous melanomas on the foot, and compared these to 26 patients who underwent either secondary intention healing (SIH, n  = 13) or NPWT ( n  = 13) alone. The punch grafting with NPWT group showed significantly shorter healing times than those of the other two groups. Evaluation of completely healed wounds using the Vancouver Burn Scar Assessment Scale revealed that the punch grafting group had mean values better, or comparable, to the SIH or NPWT group in four of the five scales (except pigmentation). As for complications, only one patient developed a wound infection after punch grafting. Further, by utilizing NPWT for fixation of punch grafts, it was possible to treat all subjects as outpatients after punch grafting. These results show that a combination treatment of NPWT and punch grafting is an excellent therapeutic option for post‐wide excision wounds on the feet, with significantly shortened healing times and favorable cosmetic outcomes.